Effective group discussion theory and practice - Galanes, Gloria J.; Adams, Katherine (Katherine L.) (McGraw-Hill Education, 2019)
"Effective Group Discussion focuses on secondary groups, such as work groups, committees, task forces, self-directed work teams, and other small groups with tasks to complete. The text provides practical tips and also serves well as a reference source for advanced communication students, consultants, or group leaders"--